Concise Total Synthesis of Complanadine A Enabled by Pyrrole-to-Pyridine Molecular Editing - Martin, Brandon S.; Ma, Donghui; Saito, Takeru; Gallagher, Katelyn S.; Dai, Mingji (Synthesis, 2023)
The Lycopodium alkaloid complanadine A, isolated in 2000, is a complex and unsymmetrical dimer of lycodine. Biologically, it is a novel and promising lead compound for the development of new treatments for neurodegenerative disorders and persistent pain management. Herein, we report a concise synthesis of complanadine A using a pyrrole-to-pyridine molecular editing strategy. The use of a nucleophilic pyrrole as the precursor of the desired pyridine enabled an efficient and one-pot construction of the tetracyclic core skeleton of complanadine A and lycodine. The pyrrole group was converted into a 3-chloropyridine via Ciamician–Dennstedt one-carbon ring expansion. A subsequent C–H arylation between the 3-chloropyridine and a pyridine N-oxide formed the unsymmetrical dimer, which was then advanced to complanadine A. Overall, from a readily available known compound, the total synthesis of complanadine A was achieved in 11 steps. The pyrrole-to-pyridine molecular editing strategy enabled us to significantly enhance the overall synthetic efficiency. Additionally, as demonstrated by Suzuki–Miyaura cross-coupling, the 3-chloropyridine product from the Ciamician–Dennstedt rearrangement is amenable for further derivatization, offering an opportunity for simplified analogue synthesis.
Keywords: total synthesis; molecular editing; alkaloids; complanadine; ring expansion